Lavagem de Capitais: a importância da atividade notarial no combate à corrupção do Estado - Zimmermmann, Marcial Luís (Universidade do Vale do Rio dos Sinos, 2019)
This work has as objective to analyze the effectiveness of the notarial activit instrumentalisation as a way of combating money laundering in the Brazilian legal system, as preventing corruption of the State through the dignification of the repression to the illicitudes that shake the national financial system. In general, it will be sought to analyze the historical and contemporary characteristics of extrajudicial services in the perspective of the existence of Comparative Law and Brazil's adherence to the system of International Legal Cooperation. In order to do so, the main bodies to combat transnational crimes of concealment of assets, rights and values will be elucidated by making possible a concrete conception of what is necessary to adapt the national regime within reach of the effective indices of European countries such as Spain. Finally, the Spanish anti-money laundering system will be used as a benchmark, drawing conceptual elements on the differences found in the Centralized Protection Body, SEPBLAC and COAF and CENSEC, suggesting the possible future use of Blockchain's technology as an alternative to encrypt and unalterably record all the information necessary for the concrete adoption of the conduits necessary to identify the suspicious operations, directing them in a filtered way and automatic to the competent authorities for the verification and repression of money laundering. We used the phenomenological-hermeneutic research method whose execution has analytic-descriptive forays. It was observed, therefore, that the current configuration of the Brazilian model does not effectively consider the mandatory subjection of extrajudicial services, resulting in inefficiency.
Keywords: Atividade notarial; Blockchain; Crime; Combate; Efetividade; Função pública; Lavagem de dinheiro; Prevenção; Regulamentação; Unificação de dados; Notary activity; Blockchain; Crime; Combat; Effectiveness; Public function; Money laundry; Prevention; Regulation; Unification of data; ACCNPQ::Ciências Sociais Aplicadas::Direito